2011
DOI: 10.1002/j.1551-8833.2011.tb11384.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloride‐to‐sulfate mass ratio: Practical studies in galvanic corrosion of lead solder

Abstract: The effect of the chloride‐to‐sulfate mass ratio (CSMR) on lead leaching from 50:50 lead–tin solder galvanically coupled to copper in stagnant conditions was examined using bench‐scale testing and data from water utilities. The CSMR was significantly altered by coagulant changeover, blending of desalinated seawater, anion exchange, and NaCl brine leaks from onsite hypochlorite generators. Consistent with previous experiences, increasing the CSMR to the range of 0.1 to 1.0 produced dramatic increases in lead le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 20 publications
1
76
0
Order By: Relevance
“…Further, it would be anticipated that the PACl treated water (CSMR of 2) would correlate with a higher lead release, as the CSMR level was more than double that of the other two water conditions ( Table 1). As expected based on observations by Nguyen et al [6] and Wang et al, [23] these trends were not observed given that CSMR was above the threshold of 0.5 in all waters tested. However, very significant trends were observed relative to the levels of coagulant residual present in water after simulated coagulation treatment.…”
Section: Analytical Proceduressupporting
confidence: 56%
See 2 more Smart Citations
“…Further, it would be anticipated that the PACl treated water (CSMR of 2) would correlate with a higher lead release, as the CSMR level was more than double that of the other two water conditions ( Table 1). As expected based on observations by Nguyen et al [6] and Wang et al, [23] these trends were not observed given that CSMR was above the threshold of 0.5 in all waters tested. However, very significant trends were observed relative to the levels of coagulant residual present in water after simulated coagulation treatment.…”
Section: Analytical Proceduressupporting
confidence: 56%
“…Stagnation times were chosen based on previous research conducted in this field, with the intention of representing the long stagnation times that commonly occur in public buildings over weekends. [6] Over the 27-week duration of the experiment, the samples obtained after each water change were analyzed for bulk water pH, total lead content and chloride and sulfate levels. After week 17, samples were filtered through 0.45-mm pore size PES, polysulfone filters (Maine Manufacturing, Stanford, ME, USA) and analyzed for dissolved lead and copper concentrations.…”
Section: Experimental Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…After six weeks of the experiment, for pipes with plastic and brass couplings, the CSMR was increased from its original value of 0.7 to an elevated value of 7.0 for four weeks (Table 1). The value of 0.7 is near the boundary where CSMR was found in previous research to result in enhanced galvanic corrosion (Nguyen et al, 2011c).…”
Section: Methodsmentioning
confidence: 65%
“…However, recent studies suggest that galvanic Pb:Cu connections might respond differently to phosphate, in that several studies demonstrated much higher lead after addition of phosphate in small-scale tests starting with new materials (Nguyen et al, 2011a;Arnold Jr. 2011). Chloride-tosulfate mass ratio (CSMR) of 0.5 or higher is directly associated with galvanic corrosion of solders (Nguyen et al, 2011b) and lead pipes connected to copper .…”
Section: Introductionmentioning
confidence: 96%